PERENCANAAN KONSEP MINAPOLITAN DI KAWASAN TAMBAK LOROK, SEMARANG UTARA - Sintia Dewi Wulanningrum; Theresia Budi Jayanti (Diponegoro University, 2016)
Minapolitan region is an economic region consisting of production centers, marine and fishery commodities, services, housing and other related activities. Tambak Lorok is one of fishing villages which is that located on the coastline of Java Sea in Tanjung Mas, North Semarang. The main function of Tambak Lorok is as residential areas, ponds and trades especially seafood. The main issues in Tambak Lorok are: the rob, low economy, and less infrastructure. The concept of minapolitan is used to improve the local economy of coastal communities through agribusiness subsystems and its supporting subsystems. This study employed descriptive qualitative method.